Impact of IL1, IL6, IL8, IL17 and TGF Gene Polymorphisms in Bladder Cancer Patients - Hamsa Ahmed Jasim (Journal of Global Pharma Technology, 2018)
Bladder cancer is one of the most common cancers worldwide and the most frequent malignancy of the urinary tract recently, several single nucleotide polymorphisms (SNPs) have been identified in cytokine gene sequences, particularly within the promoter region of these genes, and have been shown to be associated with the development of bladder cancer. The present study investigates the association of IL1, IL6, IL8, IL17 and TGF polymorphisms with the incidence of bladder cancer. Blood samples were collected from 50 histologically confirmed adult patients with bladder cancer and 28 apparently healthy individuals. DNA was extracted from each blood sample, and the genes were amplified using polymerase chain reaction (PCR) with gene-specific primers target. Systemic IL1β, IL6, IL8, IL17 and TGFβ, concentration was assessed in serum samples from each participant by enzyme-linked immunosorbent assay (ELISA). A appositive association between The allele T of the SNP rs 16944 of IL 1 gene (P=0.005, OR=4.263, 95%CI=1.566-11.603) and the allele G of the SNP rs 1800469 of TGF β gene (OR=0.19, 95% CI=0.035-1.02) were found. These data indicate an etiological role of IL-1β and TGF gene polymorphism in bladder cancer.Keywords: Single nucleotide polymorphism (SNPs), Interleukin, TGF, bladder cancer.